Answer and Step-by-step explanation:
[tex]Hello~let's~solve~your~equation:[/tex]
Step 1: Simplify both sides of the equation:
[tex](\frac{4}{5}) (x)+(\frac{4}{5})(\frac{5}{6})+\frac{-2}{3}x+\frac{1}{6} =\frac{7}{6}[/tex] [tex](Distribute)[/tex]
[tex]\frac{4}{5}x+\frac{2}{3}+\frac{-2}{3}x+\frac{1}{y\6}=\frac{7}{6}[/tex]
[tex](\frac{5}{5}x+ \frac{-2}{3}x )+(\frac{2}{3}+ \frac{1}{6})=\frac{7}{6}[/tex] [tex](Combine~like~terms)[/tex]
[tex]\frac{2}{15}x+\frac{5}{6}=\frac{7}{6}[/tex]
Step 2: Subtract 5/6 from both sides:
[tex]\frac{2}{15}x+\frac{5}{6}- \frac{5}{6} =\frac{7}{6} -\frac{5}{6}[/tex]
[tex]\frac{2}{15}x=\frac{1}{3}[/tex]
Step 3: Multiply both sides by 15/2:
[tex](\frac{15}{2}) *(\frac{2}{15}x)=(\frac{15}{2})*(\frac{1}{3})[/tex]
[tex]x=[/tex] [tex]\frac{5}{2}[/tex]